2018
DOI: 10.1007/s10916-018-0978-6
|View full text |Cite
|
Sign up to set email alerts
|

Development of Improved Software Intelligent System for Audiological Solutions

Abstract: Of late, there has been an increase in hearing impairment cases and to provide the most advantageous solutions to them is an uphill task for audiologists. Significant difficulty faced by the audiologists is in effective programming of hearing aids to provide enhanced satisfaction to the users. The main aim of our study was to develop a software intelligent system (SIS): (i) to perform the required audiological investigations for finding the degree and type of hearing loss, and (ii) to suggest appropriate value… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…The study by Rajkumar S. and colleagues used artificial neural network methods to determine the hearing loss value and the appropriate hearing aid gain value. It was reported that 86% of individuals with hearing impairments were satisfied with the gain values recommended by the studies [10].…”
Section: Literature Reviewmentioning
confidence: 97%
“…The study by Rajkumar S. and colleagues used artificial neural network methods to determine the hearing loss value and the appropriate hearing aid gain value. It was reported that 86% of individuals with hearing impairments were satisfied with the gain values recommended by the studies [10].…”
Section: Literature Reviewmentioning
confidence: 97%
“…Nonetheless, in (Or, et al, 2018) it is proposed that most of the modern and/or state-of-the-art health information systems still face challenges in terms of their output which is less efficient, and that is due to their under-explored techniques (or approaches) underlying the design of the systems (Nogueira, et al, 2018). In (Rajkumar, et al, 2018), there is a proposed improved software intelligent system towards enhancing the performance of a hearing impairment system in which the system is aimed to provide solution to audio logical problems. In (Singh, et al, 2017) is an introduced deep learning model towards recognition of human activity in which the model is able to learn to classify human activities without prior knowledge.…”
Section: Introductionmentioning
confidence: 99%
“…Notwithstanding, Or et al [14] propose that most of the modern health information systems have under-explored design technique challenges [5]. Moreover, Rajkumar et al [15] propose an improved software intelligent system towards enhancing the performance of a hearing impairment system to provide a solution to audiological problems. Whereas, Singh et al [16] introduce a deep learning model towards human activity recognition such that without prior knowledge the model can be used to classify human activities.…”
Section: Introductionmentioning
confidence: 99%